Ciclagem de nutrientes e energia por processos baseados em microalgas a partir das águas residuais do abate e processamento de aves e suínos - Santos, Alberto Meireles dos (2018)
The nutrient cycling from microalgae-based processes is a potential technological route to be applied in wastewater treatment plants. Therefore, the objectives of this research are: (a) develop a bioreactor applicable to conversion of organic matter, nitrogen and phosphorus into products of microalgal metabolism; (b) evaluate the kinetics of biomass production; (c) evaluate the kinetics of organic matter and nutrients consumption (nitrogen and phosphorus); (d) carry out material balances and analyzes of economic potential of the process and bioproducts; (e) determine the quantitative and qualitative composition of biomass and production of bioproducts; (f) determine biomass composition of biomass; (g) determining fatty acid profile of biomass; and (h) characterize biodiesel from microalgal biomass. The nutrient cycling by Phormidium autumnale in agroindustrial wastewater indicate high removal efficiencies of 97.6%, 85.5% and 92.4% for COD, N–TKN and P–PO4–3, respectively, in parallel to a microalgal sludge productivity of 0.27 kg/m3/d. The economic analysis demonstrated a cost of USD 2.66/m3 of treated industrial wastewater, and as consequence of this process, the production cost of microalgal sludge was USD 0.03/kg of dehydrated biomass. The generated microalgal sludge shows predominance of saturated fatty acids, indicates the potential of its use as a suitable lipid input for biodiesel synthesis. The lipid-extracted microalgae (LEM) showed high content of free amino acids, minerals and pigments, being a potential source for animal feed. Thus, the heterotrophic microalgae cultivation in wastewater has demonstrated to be capable of removing pollutants and, simultaneously, producing biofuel and being a potential source for animal feeding from microalgal sludge, a profit margin of 94% can be obtained.